Successful delivery in a case of sickle cell disease with bilateral avascular necrosis: a case report - Mukherjee, Susmita; Bhalla, Amit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Sickle cell disease is an inherited hemoglobinopathy. The patients with sickle cell disease had a small life years, before the advancement of medical science and development of newer drugs. These have improved the life expectancy among the sickle cell disease patients. Females are reaching reproductive age and are expectant of becoming mothers. But pregnancy in a sickle cell disease carries major fetal and maternal complications. Managing the pregnancy from conception to delivery is a difficult task and needs a team effort. Here we presented a case report of a female who got pregnant without any planning and was already on hydroxyurea. On top of that she was not willing to get her pregnancy terminated.